(untitled) - Kartalopoulos, Stamatios V. (New York, 2001)
Enhance your understanding of the failure mechanisms of optical components, and draft fault detection guidelines to design a robust Dense Wavelength Digital Multiplexing (DWDM) system and network that exhibits and maintains optical signal quality and system reliability.
Keywords: Optical communications,Wavelength division multiplexing,Signal processing,Truyền thông quang học,Sóng viễn thông,Tín hiệu chế biến; Digital techniques,Kỹ thuật số